Mesoporous TiO2: Comparison of Classical Sol-Gel and Nanoparticle Based Photoelectrodes for the Water Splitting Reaction - Hartmann, Pascal; Lee, Doh-Kwon; Smarsly, Bernd M.; Janek, Juergen (AMER CHEMICAL SOC, 2010)
This paper describes a systematic comparison of the photoelectrochemical properties of mesoporous TiO2 films prepared by the two most prevalent templating methods: The use of preformed, crystalline nanoparticles is generally considered advantageous compared to the usage of molecular precursors such as TiCl4, since the latter requires a separate heat treatment at elevated temperature to induce crystallization. However, our photoelectrochemical experiments clearly show that sol-gel derived mesoporous TiO2 films cause an about 10 times higher efficiency for the water splitting reaction than their counterparts obtained from crystalline TiO2 nanoparticles. This result indicates that for electrochemical applications the performance of nanoparticle-based metal oxide films might suffer from insufficient electronic connectivity.
Keywords: PHOTOCATALYTIC ACTIVITY; NANOCRYSTALLINE TIO2; ANATASE TIO2; HYDROGEN GENERATION; NANOTUBE ARRAYS; THIN-FILMS; CRYSTALLINE; SEMICONDUCTOR; CONDUCTIVITY; EFFICIENCY